114k views
4 votes
Add the following
-3a2b2, (–5/2) a2b2, 4a2b2, and (⅔) a2b2​

User SJaka
by
6.3k points

1 Answer

12 votes

Given:

The terms are
-3a^2b^2,-(5)/(2)a^2b^2,4a^2b^2,(2)/(3)a^2b^2.

To find:

The sum of given terms.

Solution:

Sum of given terms is


-3a^2b^2+(-(5)/(2)a^2b^2)+4a^2b^2+(2)/(3)a^2b^2


=-3a^2b^2-(5)/(2)a^2b^2+4a^2b^2+(2)/(3)a^2b^2

Taking out common factors, we get


=\left(-3-(5)/(2)+4+(2)/(3)\right)a^2b^2


=\left((-18-15+24+4)/(6)\right)a^2b^2


=\left((-5)/(6)\right)a^2b^2


=(-5)/(6)a^2b^2

Therefore, the sum of given terms is
(-5)/(6)a^2b^2.